Antiretroviral Treatment in HIV-1-Positive Mothers: Neurological Implications in Virus-Free Children. - Coelho, Antônio Victor Campos; Tricarico, Paola Maura; Celsi, Fulvio; Crovella, Sergio (Int J Mol Sci, 2017)
Since the worldwide introduction of antiretroviral therapy (ART) in human immunodeficiency virus type 1, HIV-1-positive mothers, together with HIV-1 testing prior to pregnancy, caesarian birth and breastfeeding cessation with replacement feeding, a reduction of HIV-1 mother-to-child transmission (MTCT) has been observed in the last few years. As such, an increasing number of children are being exposed in utero to ART. Several questions have arisen concerning the neurological effects of ART exposure in utero, considering the potential effect of antiretroviral drugs on the central nervous system, a structure which is in continuous development in the fetus and characterized by great plasticity. This review aims at discussing the possible neurological impairment of children exposed to ART in utero, focusing attention on the drugs commonly used for HIV-1 MTCT prevention, clinical reports of ART neurotoxicity in children born to HIV-1-positive mothers, and neurologic effects of protease inhibitors (PIs), especially ritonavir-"boosted" lopinavir (LPV/r) in cell and animal central nervous system models evaluating the potential neurotoxic effect of ART. Finally, we present the findings of a meta-analysis to assess the effects on the neurodevelopment of children exposed to ART in utero.
Keywords: Animals; Anti-HIV Agents; Antiretroviral Therapy, Highly Active; Disease Management; Disease Models, Animal; Epigenesis, Genetic; Female; HIV Infections; HIV-1; Humans; Infectious Disease Transmission, Vertical; Maternal Exposure; Meta-Analysis as Topic; Mothers; Neurodevelopmental Disorders; Pregnancy; Prenatal Exposure Delayed Effects